APPLICATION OF CT-SCAN IN CORE ANALYSIS - Septi Anggraeni; Indra Jaya (Scientific Contributions Oil and Gas, 2000)
Computerized tomography (CT) is a new radiological imaging technique that measures density and otomic composition inside object. Since 1980, the CT has been applied in petrophysics and reservoir engineering. This paper discusess several petrophysica application in core analysis such as: quantification of complex mineralogy, characterixation drilling fluid invasion core quality control bedding detection, porosity determination, and fracture analysis.